Concomitant atopic dermatitis and narcolepsy type 1: psychiatric implications and challenges in management - Justin Chin; Craig Bearison; Nanette Silverberg; Mary Lee Wong (General Psychiatry, 2019)
Atopic dermatitis (AD) and narcolepsy type 1 (NT1) are two distinct diseases that have not been classically shown to be related. The potential connection between the known immunological aetiology of AD and the proposed autoimmune pathophysiology of dysregulation in NT1; however, is the subject of ongoing speculation and debate with advances in gene sequencing and technology. Here, we present a case of a patient with concomitant refractory AD and NT1 and review the current research on their immunological relationship and the challenges in management relative to disease burden and psychiatric comorbidities.